Analysis Of Phonological Errors In The Program "Lapor Pak!" - Larasati Dwi Wahyuni; Maulia Hafizah; Yani Lubis (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
This research aims to describe phonological errors in the television program "Lapor Pak!" on the private television station Trans 7. This study is a qualitative research with a qualitative descriptive method. The data source of this research includes all utterances delivered by the hosts, invited guests, or speakers in the program "Lapor Pak!". The data collection technique used in this study is observation and note-taking. The analysis technique employed in this research is qualitative data analysis, which involves identifying, classifying, analyzing, and drawing conclusions from the research findings. The researcher found nine phonological errors, namely metathesis, monophthongization, apheresis, neutralization, zeroization, assimilation, vowel modification, epenthesis, and syncope.